Economic Evaluation of Benefits and Value of Indigenous Vegetables Grown in Kuyaimee Sub-district of Sanam Chaikhet District of Chachoengsao Province - รัตนวิไล, รุ่งฤดี (Business Administration and Management Journal Review, 2016)
This research aims to study the benefits of indigenous vegetables based on a self-sufficient theory and to evaluate the economic values of the indigenous vegetables Sub-district of Sanam Chaikhet District of Chachoengsao Privince. The population of this study was 87 gardeners who have cultivated indigenous vegetables for selling with an organic agriculture group in Kuyaimee sub-district, Sanam Chaikhet district in Chachoengsao province. They have gotten direct benefits from 155 indigenous vegetables for their own consumption and income earning. Data were collected with interviews and analyzed by descriptive statistic, t-test and one-way ANOVA. The research found that the most gardeners were female with age between 41 – 60 years old, had family members around 4 – 6 people and the land for cultivation around 1 – 15 rai. The margin profit from selling indigenous vegetable was about 100 to 1,000 baht per year. The economic values of indigenous vegetable can be divided into three groups—1) for own consumption calculated as 123,122.4 baht per year, 2) for selling to the organic agricultural group calculated as 479,825.20 baht per year, and 3) for value adding calculated as 33,764 baht per year. Furthermore, the statistic shown that there were not a significant difference of the values of indigenous vegetables among different genders, ages and the number of family member at alpha 0.05 (t = .126, .270 and .554) Meanwhile, there was a significant different of valued of indigenous vegetable selling between gardener who had different cultivation size at 0.05 (F = 85.88 9)